Electrogeneration of Hydrogen Peroxide via Oxygen Reduction on Polyindole Films. Issue 8 (20th April 2020) - Warczak, Magdalena; Osial, Magdalena; Berggren, Magnus; Głowacki, Eric Daniel
Abstract : Efficient electrochemical generation of hydrogen peroxide via oxygen reduction is of great interest for industrial and clean energy applications. In this work, we report the application of conducting polymer—polyindole (PIN) films for electrogeneration of hydrogen peroxide. Polyindole films were electrochemically polymerized on gold substrates in non-aqueous electrolytes and then tested for electrocatalytic properties in acidic aqueous solutions. We find that PIN can serve as an electrocatalyst for oxygen reduction reaction via a two-electron pathway. Electrolysis performance indicates that PIN is an efficient, selective, and stable electrocatalyst for hydrogen peroxide generation at low pH, and suggests PIN as a conducting polymer with useful electrocatalytic properties in scientific experiments and applications.